RTHP-32. FIRST EXPERIENCE WITH GAMMATILE PERMANENT IMPLANTS FOR RECURRENT BRAIN TUMORS. (11th November 2019) - Ferreira, Clara; Alaei, Parham; Chen, Clark; Reynolds, Margaret; Sterling, David; Dusenbery, Kathryn
Abstract: Gammatile TM permanent brachytherapy implants have been FDA cleared for patients with recurrent brain tumors. We report our experience with the first 6 patients with recurrent high grade primary brain tumors treated with re-resection and implantation. Each tile contains 4 encapsulated radioactive Cs-131 seeds embedded in collagen. To determine the number of tiles needed, the potential tumor cavity surface area was estimated using the preoperative MRI images. The anticipated cavity surface area was calculated, the surface area of anticipated surgical approach was subtracted. This area was divided by 40mm 2 (tile area) and this number of tiles were ordered. At the time of surgery, after maximal safe tumor resection, tiles were placed into the resection cavity and the surgical cavity closed as usual. On post-implant day 1, CT and MRI scans were performed. The cavity was contoured, then expanded by 5mm to create HRCTV. T1 MRI enhanced lesions were contoured as residual GTV (GTVr ). A dose of 60Gy over the course of treatment was prescribed to HRCTV. In each of these 6 cases, over 95% of the HRCTV was covered by the 60Gy isodose surface, and GTVr D90 ranged from 22.9Gy to 113.8Gy. The additional time required for the tile placement in all cases was less than 10 minutes. Post-operatively exposure rates at 1m were less than 6 mR/hr (ranging from 1.3 to 3.2mR/h). Permanent GammaTile for recurrent brain tumors is a viable option for selected previously irradiated patients who are operative candidates. Benefits include irradiation of the tumor bed starting immediately after resection with no need to wait for wound healing, and no need to subsequently surgically remove the tile. We were able to accurately predict the number of tiles needed, although in one case collagen spacers were utilized. Due to low exposure rates, radiation protection issues are very manageable.